Fragmentation OF Landholdings in Rural Salamieh District (Journal of Hama University, 2020)
Agriculture is still the main source of income in the Salamieh district, but it has fallen back sharply in recent years as a major source of income, which becoming a secondary source of many agricultural households that have moved to other jobs such as government jobs, business, etc.The fragmentation of the landholdings in Salamieh district is a significant problem that farmers have suffered for decades without any solutions. Therefore, this research aimed to characterize the problem of fragmentation of the landholdings in Salamieh district and to identify its size as well as its causes, and to identify the impact of current situation of landholdings on farms’ income.A research questionnaire has been collected by individual interview. The villages of Tel aldra, Berri al-Sharqi, and Aqareib al-Safi were the sample of study at 26, 27 and 27 households per village, respectively.The main results of the study were:- Statistical analysis showed significant differences between the three villages with regard to average of agricultural landholdings.- The value of Gini coefficient was (0.55), which indicates inequality of distribution of landholdings within the study sample.- The most important variables that affecting the agricultural income, Were the area of ​​the largest agricultural plot, the area of ​​ lost land, the distance between farm and the house, and the number of owned agricultural machineries.- The correlation coefficient showed a very significant correlation between agricultural income and the area of ​​the largest agricultural plot (0.80 **).